PERAN KINERJA KEUANGAN DALAM MEMPREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR ENERGI - MULIYANA; HENDRA (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
This study aims to empirically examine the influence of cash flow, leverage, asset tangibility, liquidity, and profitability on financial distress among companies. The research focuses on energy sector firms listed on the Indonesia Stock Exchange (IDX) over the period from 2015 to 2024. A purposive sampling method was applied to select the sample based on specific criteria, resulting in 9 companies out of 87 meeting the requirements. The analysis was carried out using panel data regression with the common effect model, processed through EViews 12 software.The findings reveal that cash flow, leverage, asset tangibility, and liquidity have no significant effect on financial distress. In contrast, profitability shows a significant and positive impact, indicating that higher levels of profitability are associated with a lower risk of financial distress. This is in line with the interest coverage ratio (ICR) concept, where increased profitability, reflected through higher EBIT, enhances the firm's ability to meet interest obligations, thereby suggesting a healthier financial condition and reduced likelihood of distress.